2019
DOI: 10.1007/jhep06(2019)015
|View full text |Cite
|
Sign up to set email alerts
|

Gluon helicity flip in a plane wave background

Abstract: We compute the leading probability for a gluon to flip helicity state upon traversing a background plane wave gauge field in pure Yang-Mills theory and QCD, with an arbitrary number of colours and flavours. This is a one-loop calculation in perturbative gauge theory around the gluonic plane wave background, which is treated without approximation (i.e., to all orders in the coupling). We introduce a background-dressed version of the spinor helicity formalism and use it to obtain simple formulae for the flip amp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 85 publications
0
33
0
Order By: Relevance
“…The spinor helicity formalism for massless fields in a trivial background is now a widely used tool in the scattering amplitudes community (cf., [69,70]). In [63], we showed that the spinor helicity formalism extends naturally to massless fields in plane wave backgrounds, and this plays a crucial role in new allmultiplicity formulae for gluon and graviton scattering in chiral plane waves [28].…”
Section: Four-dimensions and Spinor Helicitymentioning
confidence: 99%
See 4 more Smart Citations
“…The spinor helicity formalism for massless fields in a trivial background is now a widely used tool in the scattering amplitudes community (cf., [69,70]). In [63], we showed that the spinor helicity formalism extends naturally to massless fields in plane wave backgrounds, and this plays a crucial role in new allmultiplicity formulae for gluon and graviton scattering in chiral plane waves [28].…”
Section: Four-dimensions and Spinor Helicitymentioning
confidence: 99%
“…Such quantities are universal for three-point amplitudes on plane wave backgrounds (cf., [46,62,63]).…”
Section: Gluon Emission Amplitudementioning
confidence: 99%
See 3 more Smart Citations